The influence of social media on English language learning and academic performance at undergraduate level - Ali, Zeeshan (Journal of Language, Literature, Social and Cultural Studies, 2023)
This research article imparts new and current knowledge about the essential characteristics of the influence of social media especially Facebook, and YouTube on the English language learning and academic performance of BS English students. The questionnaire was used as a research instrument to collect the data from the sample students. The questionnaire was developed online using the Google drive option. The developed questionnaire was shared with sample students through WhatsApp, Email, and social media. The sample of this study was 64 students of the University of Lahore who were studying in the BS English program. A convenient sampling technique was used to collect data. The nature of this research was quantitative. The descriptive and inferential statistics were applied to the collected data to get the results. The analyzed data revealed the findings concerning grammatical and vocabulary problems, health issues, poor results, assignments, exams, and downloading of material relevant to English language structure and use. The researcher concluded that social media influences English language education permanently. Future researchers should use and implement large sample and broader area.